A case study with aim to know impact development of port of fishery to absorbtion of labour and earnings of vinicity society has been conduct in August till Octooer 2004. Research executed at society around Port of Fishery of Coast of Lempasing, 8andar Lampung. Determination of respondent at the location port of fishery selected by using purposive sampling method. Data collecting use some materials assist by questionaire. Overall \jf data was analyzed, through either deScriptive and statistic. R - Helmi Yusuf; Kooswardhono Moedikdjo; M Sri Saeni; Lutfi I Nasution (Buletin Ekonomi Perikanan, 2005)
A case study with aim to know impact development of port of fishery to absorbtion of labour and earnings of vinicity society has been conduct in August till Octooer 2004. Research executed at society around Port of Fishery of Coast of Lempasing, 8andar Lampung. Determination of respondent at the location port of fishery selected by using purposive sampling method. Data collecting use some materials assist by questionaire. Overall \jf data was analyzed, through either deScriptive and statistic. Result of research indicated that various society group pursuant to the kind of livelihood (fisherman, trader, labour, farmer and fish processor) express that development of port of fishery of coast of Lempasing have positive impact due to absorbtion of labour and improvement of earnings of the vinicity society. The absorbtion of society in some livelihood such fisherman, traders, labour and fish processor are subsequently increase until 90,63%, 73,31%, 82,81% and 29,63%. While, the absorption of labor force in farmer has indicated that the farmer was decline until 40,63%. Improvement of biggest earnings seen at fISh trader society group 113,41 %, while earnings of fldh processor and labour fish up to 101,08% and 54,07%. Improvement of earnings also happened in farmer society group by up to 102,50%. Despite, the improvement of earnings at fisherman SOCiety happened with smallest percentage that is only 44,93%.